Universiti Teknologi MARA Kampus Mukah - Abang Sawli, Abang Aswandi (Universiti Teknologi MARA, Sarawak, 2016)
As a requirement report for the semester 2 students of Diploma in Plantation and Agriculture Technology, we are required to complete and submit our industrial training report for the subject FPA210 Industrial Training. The subject FPA210 Industrial Training must be taken by all students of MARA University of Technology (UiTM) in order to ensure that the students are able to obtain knowledge and exposures in the field of practical as well as to introduce some of the basic techniques and tools that can be used by future executive office in managing their estate All knowledge obtained in the midst of preparing this can be used by the students to face the complex and challenging business world when they have graduated.